Prevalence and Incidence of Staphylococcus aureus from Wound of Different Animal Species - Mussarat Kumbhar,; Safia Kandhro,; Rehmatullah Rind,; Rameez Raja Kaleri,; Iqra Shafi Chandio,; Tanzila Farooq,; Asif Rehman,; Aijaz Junejo,; Faisal Noor Qureshi ,; Mathan Kumar, (Journal of Basic & Applied Sciences, 2018)
The prevalence incidence and biochemical characteristics of Staphylococcus aureus isolated from wounds of buffalos, goats, dogs, donkeys and chickens were studied during present indigestion.The highest infection of Staphylococcus aureus was found in wound samples of buffalos (70.00%). as compared to goat, (33%), dog, (3%) donkey (40%) and chicken, (46.66%) respectively. The overall pure samples with Staphylococcus auerus from the animals was recorded as 39.13% while mixed infection was observed as 34.78%. The shape of Staphylococcus auerus isolated from buffalos, goat, and chicken were cocci, spherical, round in shape and characterized as G+ve. The Staphylococcus auerus isolated from all the animals were non-motile. It is concluded that highest infections of Staphylococcus aureus was found in buffalo (70.00%), whereas highest number of Staphylococcus aureus bacterial specie was observed as compared to other bacterial species.